Socioeconomic and cultural factors associated with pap smear screening among French women living in Réunion Island - Rémi Houpert; Marc-Karim Bendiane; Laetitia Huiart; Anne-Deborah Bouhnik; Caroline Alleaume; Rajae Touzani; Jacqueline Veronique-Baudin; Julien Mancini; Clarisse Joachim; Emmanuel Chirpaz (BMC, 2024)
Abstract Background Réunion Island is a French overseas territory located in the southern Indian Ocean, with a challenging socioeconomic and multicultural context. Compared to mainland France, Réunion has an overincidence and overmortality of cervical cancer. In order to investigate these two issues, it is important to evaluate the barriers and potential levers to Pap smear screening among female inhabitants of the island. We aimed to identify the specific socio-demographic factors, cultural factors, and living conditions associated with Pap smear screening in Réunion, with a view to increasing uptake. Methods We conducted a Knowledge Attitude Behavior and Practices (KABP) survey on cervical cancer screening practices among women aged between 25 and 65 years old living in Réunion Island, selected using random digit dialing sampling. Data were collected using Computer Assistant Telephone Interviews. Weighted chi-squared tests and Student's t-tests were used to compare women who had up-to-date Pap smear screening with women who did not. Weighted logistic models were used to identify the factors associated with not having up-to-date screening. Results A total of 1000 women were included in the study. Of these, 88.1% had a Pap smear test during the previous three years. Factors independently associated with not being up to date were as follows: aged over 55 (AOR 2.3 [1.2-4.3]), no children (AOR 2.5 [1.4-4.3]), having free universal health coverage (AOR 1.7 [1.1-2.7]), an income per unit consumption lower than 1500€ per month (AOR 2.0 [1.1-3.7]), low health literacy (AOR 2.7 [1.7-4.1]), not consulting a general practitioner in the prior 12 months (AOR 3.6 [2.0-6.5]), and a BMI > 30 (AOR 2.6 [1.5-4.4]). Conclusions This is the first large-scale survey focusing on recommended Pap smear screening uptake in Réunion Island. Although self-reported screening incidence was higher than in mainland France, national screening policies must take into account the island's diverse social and cultural characteristics (e.g., an ageing population, low health literacy), while implementing actions to fight against poverty and increase general access to healthcare.